2012
DOI: 10.4174/jkss.2012.82.5.281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognostic factors in papillary thyroid microcarcinoma depends on age

Abstract: PurposeClinical outcomes of papillary thyroid microcarcinoma (PTMC) vary. In general, age at diagnosis is an independent prognostic factor in conventional papillary thyroid carcinoma. However, it is unclear in patients of PTMC. The purpose of this study was to identify clinicopathologic features and prognostic factors of PTMC according to patients' age.MethodsFive hundred twenty-seven patients who received thyroid surgery and diagnosed as having PTC between January 2001 and December 2009 were included. The cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 29 publications
4
27
2
6
Order By: Relevance
“…Recurrence rates, as reported in the literature, range from 0.94% up to 10.3%. [4][5][6]12,28,[32][33][34][38][39][40][41][42] The recurrence rate we observed is even lower at 0.5%, and the recurrent disease was found after a median of 2.4 years. Fatal outcomes from PMCs are observed even less frequently and a literature review indicates that these lie between 0% and 1%.…”
Section: Article In Presscontrasting
confidence: 63%
See 1 more Smart Citation
“…Recurrence rates, as reported in the literature, range from 0.94% up to 10.3%. [4][5][6]12,28,[32][33][34][38][39][40][41][42] The recurrence rate we observed is even lower at 0.5%, and the recurrent disease was found after a median of 2.4 years. Fatal outcomes from PMCs are observed even less frequently and a literature review indicates that these lie between 0% and 1%.…”
Section: Article In Presscontrasting
confidence: 63%
“…Multifocality is found in approximately 20-40% of the PMCs. 4,5,31,32 Our study revealed a multifocal disease in 27.5% of the patients; however, not all of our patients received radical surgery; therefore, the actual rate of multifocality could not be fully evaluated. Multifocality is generally perceived as a risk factor for lymph node metastases and disease recurrence; but there is a lack of evidence-based data to confirm this assumption.…”
Section: Article In Pressmentioning
confidence: 74%
“…28) Multifocality in PTMC is not unusual. 17) In this study, the incidence of multifocality was 24.8%. The incidence of multifocality in PTMC has been reported to be 19 to 32%.…”
Section: Statistical Analysesmentioning
confidence: 92%
“…Selain goiter yang bersifat endemik, sebagian kasus goiter yang terjadi di Indonesia bersifat non endemik. Hal ini sangat berbeda dengan insiden karsinoma tiroid di dunia barat yang lebih sering berkaitan dengan efek radiasi [16,17] Klasifikasi Goiter Secara Klinis…”
Section: Epidemiologi Goiterunclassified